Complete Solution of Electronic Excitation and Ionization in Electron-Hydrogen Molecule Scattering - Zammit, Mark; Savage, Jeremy; Fursa, Dmitry; Bray, Igor (The American Physical Society, 2016)
The convergent close-coupling method has been used to solve the electron-hydrogen molecule scattering problem in the fixed-nuclei approximation. Excellent agreement with experiment is found for the grand total, elastic, electronic-excitation, and total ionization cross sections from the very low to the very high energies. This shows that for the electronic degrees of freedom the method provides a complete treatment of electron scattering on molecules as it does for atoms.